The Saskatchwan Government’s Internal Arrangements to Accomodate Collective Bargaining - Wetzel, Kurt; Gallagher, Daniel (Relations industrielles / Industrial Relations, 1979)
This study looks at three models employee! by Saskatchewan's provincial public sector management to facilitate bargaining. First is a relatively conventional adaptation to bargaining with provincial civil servants. In the second, associations of nursing homes and hospitals bargain in the presence of a government observer. The third has the government and school trustees, with government holding the balance of power, negotiating jointly with the teachers. The paper also discusses the central coordination and control functions which the government has developed to deal with bargaining.